PERANCANGAN APLIKASI E-DISCUSSION ANTARA GURU DAN SISWA BERBASIS WEB PADA SMP N 13 SOLOK SELATAN DENGAN MENGGUNAKAN BAHASA PEMROGRAMAN PHP DAN DATABASE MySQL - Lita Gusrian; Silfia Andini; Sofika Enggari (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2016)
From the research that has been conducted at Junior High School 13 South Solok can be concluded that the system used in the junior high school is less effective , due to the learning process can only be done on condition that the meeting between students and teachers in the classroom. If the meeting does not take place the learning process cannot be done. Therefore, the presence of E-Discussion system is expected to help the learning process of students effectively. After doing some research on Junior High School 13 South Solok this by collecting data through interviews and other methods. Then the analysis of data collected by the system design tools. After the designed output design.design input , design files and E-Discussion. The results of the analysis has been conducted on the Web site of the E-Discussion with the PHP programming language.